Production of kombucha SCOBY cellulose by using tea and pumpkin peel waste as fermentation substrates a comparison study - Rusyidah Mat Zin Boestami (Tanjong Malim, 2024)
Production of kombucha SCOBY cellulose by using tea and pumpkin peel waste as fermentation substrates a comparison study by Rusyidah Mat Zin Boestami